Etätyön yhteys työkykyyn ja liikuntaan - Henkilöstöliikunnan barometrin tuloksia - Muukka, Henna (2025)
Muukka, H. (2025). The association between remote work, work ability and exercise; results from the barometer on physical activity at workplaces. The faculty of Sport and Health sciences, University of Jyväskylä, Health promotion master’s thesis. 47 p, 1 attachment.